The GLEAM 200-MHz local radio luminosity function for AGN and star-forming galaxies. (6th September 2021) - Franzen, T. M. O.; Seymour, N.; Sadler, E. M.; Mauch, T.; White, S. V.; Jackson, C. A.; Chhetri, R.; Quici, B.; Bell, M. E.; Callingham, J. R.; Dwarakanath, K. S.; For, B.; et al.
Abstract: The GaLactic and Extragalactic All-sky Murchison Widefield Array (GLEAM) is a radio continuum survey at 76–227 MHz of the entire southern sky (Declination $<\!{+}30^{°}$ ) with an angular resolution of ${≈}2$ arcmin. In this paper, we combine GLEAM data with optical spectroscopy from the 6dF Galaxy Survey to construct a sample of 1 590 local (median $z ≈ 0.064$ ) radio sources with $S_{200\, MHz} > 55$ mJy across an area of ${≈}16\, 700\, deg^{2}$ . From the optical spectra, we identify the dominant physical process responsible for the radio emission from each galaxy: 73% are fuelled by an active galactic nucleus (AGN) and 27% by star formation. We present the local radio luminosity function for AGN and star-forming (SF) galaxies at 200 MHz and characterise the typical radio spectra of these two populations between 76 MHz and ${\sim}1$ GHz. For the AGN, the median spectral index between 200 MHz and ${\sim}1$ GHz, $α_{high}$, is $-0.600 ± 0.010$ (where $S \propto ν^{α}$ ) and the median spectral index within the GLEAM band, $α_{low}$, is $-0.704 ± 0.011$ . For the SF galaxies, the median value of $α_{high}$ is $-0.650 ± 0.010$ and the median value of $α_{low}$ is $-0.596 ± 0.015$ . Among the AGN population, flat-spectrum sources are more common at lower radio luminosity, suggesting the existence of a significant population of weak radio AGN that remain core-dominated even at low frequencies. However, around 4% of local radio AGN have ultra-steep radio spectra at low frequencies ( $α_{low} < -1.2$ ). These ultra-steep-spectrum sources span a wide range in radio luminosity, and further work is needed to clarify their nature.